2022
DOI: 10.1038/s41598-022-27194-8
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends and age-period-cohort effect on adverse perinatal outcomes in Hubei, China (2011–2019)

Abstract: The increasing trend in the incidence of adverse perinatal outcomes is a public health concern globally as well as in China. However, the causes of the increasing trend are not well understood. The present tertiary-hospital-based retrospective study (2011–2019) aims to determine the secular trends and age-period-cohort effect on adverse perinatal outcomes in Hubei, China. The age-standardized incidence rates of adverse perinatal outcomes significantly decreased such as preterm births by 22% [AAPC − 3.4% (95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Many studies have shown that maternal age [37][38][39] and the number of embryos transferred [40,41] were strongly associated with perinatal outcomes in newborns, making them key confounders. To eliminate the confounding factor, we not only kept it in check during the PSM process but also performed stratified PSM analysis separately.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that maternal age [37][38][39] and the number of embryos transferred [40,41] were strongly associated with perinatal outcomes in newborns, making them key confounders. To eliminate the confounding factor, we not only kept it in check during the PSM process but also performed stratified PSM analysis separately.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, several studies have identified maternal APC effect on PTB and SGA [ 18 , 26 , 60 , 61 ]. Although our study aimed to analyse the temporal influence of LBW, PTB, and SGA births, several important limitations should be considered.…”
Section: Discussionmentioning
confidence: 99%